Prevalence and predictors of viral load non-suppression among adolescents on dolutegravir-based antiretroviral therapy: A cross-sectional study from three urban clinics, Soroti City - Connie Nait; Simple Ouma; Saadick Mugerwa Ssentongo; Boniface Oryokot; Abraham Ignatius Oluka; Raymond Kusiima; Victoria Nankabirwa; John Bosco Isunju (PLoS ONE, 2025)
Background Despite advances in HIV care, viral load suppression (VLS) among adolescents living with HIV (ALHIV) in Uganda continue to lag behind that of adults, even with the introduction of dolutegravir (DTG)-based regimens, the Youth and Adolescent Peer Supporter (YAPS) model, and community-based approaches. Understanding factors associated with HIV viral load non-suppression in this population is critical to inform HIV treatment policy. This study assessed the prevalence and predictors of viral load non-suppression among ALHIV aged 10–19 years on DTG-based ART in Soroti City, Uganda. Methods We conducted a cross-sectional study among 447 ALHIV attending three urban HIV clinics in Soroti City. Data were abstracted using a structured questionnaire and analyzed in STATA 15.0. Modified Poisson regression with robust error variance was used to identify predictors of viral load non-suppression. Adjusted relative risks (aRR) and 95% confidence intervals (CIs) were reported, with statistical significance set at p ≤ 0.05. Results Of the 447 participants, 53.5% were female, with a median age of 16 years (IQR: 14.0–17.6). The majority (72.9%) were from Soroti district and had been on DTG-based ART for a median of 42.5 months (IQR: 37.0–48.0). Most were receiving multi-month dispensing (MMD) (75.2%) and were active in care (98%). The prevalence of viral load non-suppression was 19.2% (86/447). Independent predictors of non-suppression included older age (15–19 vs. 10–14 years) (aRR: 1.69; 95% CI: 1.08–2.67), male sex (aRR: 1.48; 95% CI: 1.05–2.11), prior non-suppression before switching to DTG (aRR: 1.76; 95% CI: 1.19–2.59), use of non-fixed dose DTG regimens (aRR: 2.03; 95% CI: 1.23–3.33), history of poor adherence (aRR: 4.36; 95% CI: 2.05–9.26), and not receiving MMD (aRR: 2.83; 95% CI: 1.93–4.15). Conclusion Nearly one in five adolescents on DTG-based ART in Soroti City had viral non-suppression, despite optimized treatment regimens. Targeted interventions−particularly enhanced adherence counseling for older and male adolescents, expanding MMD coverage, and provision of fixed-dose regimens−are urgently needed to improve VLS among ALHIV. These findings underscore the need for adolescent-centered HIV care strategies to close the viral suppression gap and advance progress towards epidemic control.